2020
DOI: 10.3390/su12135425
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Irrigation Ponds to the Sustainability of Agriculture. A Review of Worldwide Research

Abstract: The use of irrigation ponds has proved to be an efficient alternative for increasing the availability and quality of water resources for irrigation and contributing to the sustainability of agriculture. This article analyses the dynamics of worldwide research on this topic over the last two decades. To do this, a review including a qualitative systematic analysis and a quantitative bibliometric analysis was carried out on a sample of 951 articles. The results reveal that this line of research is becomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 90 publications
1
25
0
Order By: Relevance
“…Furthermore, all input combinations employed in this research showed good performance. R 2 , COE, MSE and NRMSE for the training period were found 0.99, 1.00, 21245.92 and 820420.17m 3…”
Section: Rainfall Forecastingmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, all input combinations employed in this research showed good performance. R 2 , COE, MSE and NRMSE for the training period were found 0.99, 1.00, 21245.92 and 820420.17m 3…”
Section: Rainfall Forecastingmentioning
confidence: 87%
“…Water resources are crucial for agriculture, and most of the population livelihood depends on agriculture. Water storage is necessary, and the urban population's rapid growth [3,4]. The efficient and precise modeling of the rainfall-runoff process is crucial in planning water resources management [5].…”
Section: Introductionmentioning
confidence: 99%
“…The plant-soil relationship has been studied by different authors [44], revealing the relationship between certain species and some edaphic parameters: although soil fertility is often established using edaphic analysis techniques [45,46], there are no studies on the influence of nutrients on the abundance of species. For these reasons, vegetation covers, breakages, soil erosion, and water resources are studied to evaluate the environmental impact, such as soil loss and increased evapotranspiration [47][48][49]. In all cases, the authors made a diagnosis without deep knowledge about the plant-soil relationship, which moreover did not result, as in other work where for example in a contaminated soil with heavy metal, a close relationship was observed [43].…”
Section: Discussionmentioning
confidence: 99%
“…Today, a wide range of software tools are available for processing, analysing, aggregating and visualising bibliographic information [20,21]. All of this has enabled bibliometric analysis to become a methodology frequently used in disciplines as diverse as economics, agronomics, biology, engineering, medicine or psychology [22,23].…”
Section: Methodsmentioning
confidence: 99%